Self /other recognition and distinction in adolescents with anorexia nervosa: A pilot study using a double mirror paradigm - Nathalie Lavenne-Collot; Emilie Maubant; Stéphanie Déroulez; Guillaume Bronsard; Moritz Wehrmann; Michel Botbol; Alain Berthoz (PLoS ONE, 2025)
Background Abnormalities in body perception in patients affected by anorexia nervosa have been widely studied, but without explicit reference to their relationship to others and the social processes involved. Yet, there are a several arguments supporting impairments in interpersonal relationships in these patients. Notably, some evidence suggests that self/other distinction (SOD), the ability to distinguish one’s own body, actions and mental representations from those of others could be impaired. But research remains scarce in this area. Material and methods A single-centre, prospective pilot study was conducted to investigate, for the first time, self-recognition and SOD in seven adolescents with anorexia nervosa compared with matched healthy controls (HCs) using the "Alter Ego"TM double mirror paradigm. This innovative device allows the progressive morphing of one’s own face to that of another and vice versa between two subjects that interact on opposite sides of the device. Two judgement criteria were used: 1) M1: the threshold at which subjects start to recognize their own face during other-to-self morphing, and 2) M2: the threshold at which subjects start to recognize the other’s face during self-to-other morphing. In a second part, SOD was reassessed during five different sensorimotor tasks aimed at increasing body self-consciousness in participants with anorexia nervosa. Results The results showed that the participants with anorexia nervosa exhibited earlier self-recognition in the other-to-self sequence and delayed other-recognition in the self-to-other sequence. Furthermore, in contrast with that of HCs, the critical threshold for switching between self and other varied with the direction of morphing in anorexia nervosa participants. Finally, when participants with anorexia were seated in a chair with a backrest and footrest strengthening the median axis of their body, the self-recognition threshold (M1) increased significantly, approaching that of controls. Conclusions Although additional research is needed to replicate the results of this pilot study, it revealed the first behavioural evidence of altered SOD in individuals affected by anorexia nervosa through an embodied, semiecological face-recognition paradigm. The relationships between anomalies in body perception and alterations in interpersonal relationships are discussed within an integrative framework from phenomenology to neuroscience, and new research and therapeutic perspectives are presented.